Majjagni: A Classical Ayurvedic Appraisal of Marrow Metabolism and its Pathogenetic Role in Majja Pradoshaja Vikara - kaur gill, Gurpreet; yadav , Chhaju Ram; yadav , Sarika (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: In Ayurvedic physiology, Majjagni (the tissue-specific metabolic fire associated with Majja Dhatu) plays a critical role in the biotransformation, nourishment, and maintenance of bone marrow and neural tissues. Despite its critical significance, the precise physiological and pathological dimensions of Majjagni, particularly in the context of Majja Pradoshaja Vikara, remain under-defined within classical discourse.